Non-additive symmetric mixtures at selective walls - Patrykiejew, A. (Condensed Matter Physics, 2018)
The results of Monte Carlo simulation of adsorption and wetting behaviour of a highly non-additive symmetric
mixture at selective walls is discussed. We have concentrated on the interplay between the surface induced
demixing in the adsorbed films and the properties of the bulk mixture, which exhibits a closed immiscibility loop.
It has been shown that the wetting behaviour depends on the absolute values of the parameters determining
the strengths of interaction between the mixture components and the surface, as well as on their difference. In
general, an increase of the difference between the adsorption energies of the components leads to a decrease of
the wetting temperature. In the cases when the wetting of non-selective walls occurs at the temperatures above
the onset of demixing transition in the bulk, an increasing wall selectivity leads to a gradual decrease of the
wetting temperature towards the triple point, in which the vapour coexists with the mixed and demixed liquid
phases. When the wetting temperature at the non-selective wall is located below the onset of the demixing
transition in the bulk mixture, an increase of the adsorption energy of the selected component causes the
developing adsorbed films to demix and to show the reentrant mixing upon approaching the bulk coexistence.
At the temperatures above the onset of the demixing transition in the bulk, the adsorbed films remain demixed
up to the bulk coexistence and undergo the first-order wetting transition. A rather unexpected finding has been
the observation of a gradual increase of the wetting temperature at highly selective walls. Описано результати Монте Карло симуляцiй для адсорбцiї та поведiнки змочування високо неадитивної
симетричної сумiшi на селективних стiнках. Увага сфокусована на взаємозв’язку мiж поверхнево iндукованим незмiшуванням в адсорбованих плiвках i властивостями об’ємної сумiшi, яка демонструє замкнуту
петлю незмiшування. Показано, що поведiнка змочування залежить вiд абсолютних значень параметрiв,
що визначають сили взаємодiї мiж компонентами сумiшi та поверхнею, а також вiд їх рiзницi. Загалом,
збiльшення рiзницi мiж енергiями адсорбцiї компонент приводить до зменшення температури змочування. У випадках, коли змочування неселективних стiнок вiдбувається при температурах вищих, нiж
настання переходу незмiшування в об’ємi, збiльшення селективностi стiнок приводить до поступового
зменшення температури змочування до потрiйної точки, в якiй пара спiвiснує зi змiшаною та незмiшаною рiдкими фазами. Коли температура змочування на неселективнiй стiнцi знаходиться нижче настання
переходу незмiшування в об’ємнiй сумiшi, збiльшення енергiї адсорбцiї вибраного компонента змушує
адсорбованi плiвки, що утворюються, незмiшуватися та проявляти реентрантне змiшування пiсля наближення до об’ємного спiвiснування. При температурах вище точки настання переходу незмiшування
в об’ємi, адсорбованi плiвки залишаються незмiшаними аж до об’ємного спiвiснування та пiддаються
переходовi змочування першого роду. Доволi несподiваною знахiдкою виявилось спостереження поступового збiльшення температури змочування на високо селективних стiнках.